Comparison of Conventional and Flash Spark Plasma Sintering of Cu–Cr Pseudo-Alloys: Kinetics, Structure, Properties - Kirill. V. Kuskov (Metals, 2021)
Spark plasma sintering (SPS) is widely used for the consolidation of different materials. Copper-based pseudo alloys have found a variety of applications including as electrodes in vacuum interrupters of high-voltage electric circuits. How does the kinetics of SPS consolidation for such alloys depend on the heating rate? Do SPS kinetics depend on the microstructure of the media to be sintered? These questions were addressed by the investigation of SPS kinetics in the heating rate range of 0.1 to 50 K/s. The latter conditions were achieved through flash spark plasma sintering (FSPS). We also compared the sintering kinetics for the conventional copper–chromium mixture and for the mechanically induced copper/chromium nanostructured particles. It was shown that, under FSPS conditions, the observed maximum consolidation rates were 20–30 times higher than that for conventional SPS with a heating rate of 100 K/min. Under the investigated conditions, the sintering rate for mechanically induced composite Cu/Cr particles was 2–4 times higher compared to the conventional Cu + Cr mixtures. The apparent sintering activation energy for the Cu/Cr powder was twice less than that for Cu–Cr mixture. It was concluded that the FSPS of nanostructured powders is an efficient approach for the fabrication of pseudo-alloys.